Relatório de estágio supervisionado: a experiência do estágio supervisionado na usina hidrelétrica de Chavantes/SP - Clemente, Gustavo Juniel (Universidade Estadual Paulista (Unesp), 2021)
The supervised internship was carried out in the environment department of a multinational company under a Chinese concession, which is responsible for the preparation, implementation and monitoring of environmental management plans, thus meeting the conditions of the enterprise's operating license. The report shows the history of the construction of the enterprise until the period when the company was privatized and is currently under concession in China, where it manages several units focused on clean energy in Brazil. During the internship period, several administrative activities were carried out, such as the preparation of documents and technical opinions to supervisory, State and Federal bodies, activities and survey of important indicators in the field, such as hydrosedimentometric surveys and erosion processes, with the verification of the physiognomies of the slopes in areas affected by the erosion process on the banks of the reservoir, activities that must be controlled in order to mitigate adverse actions that not only compromise the generation of electricity, but also mitigate the adverse actions generated by the implementation of the project. The experience was enriching as it allowed to experience the work of the geographer in the bachelor's degree, as well as contributing to the environment in our region.

O estágio supervisionado foi realizado no departamento de meio ambiente de uma empresa multinacional sob concessão chinesa, que é responsável pela elaboração, implantação e acompanhamento dos planos de gestão ambiental, atendendo assim as condicionantes da licença de operação do empreendimento. O relatório mostra a história da construção do empreendimento até o período em que a empresa foi privatizada e hoje sob concessão da China, onde está administra diversas unidades focados emenergia limpa no Brasil. Durante o período de estágio foram realizadas diversas atividades administrativas como a elaboração de documentos e pareceres técnicos a órgãos fiscalizadores, Estaduais e Federais, atividades e levantamento de importantes indicadores em campo, como os levantamentos hidrossedimentométricos e processos erosivos, com o verificação das fisionomias dos taludes em áreas atingidas pelo processo erosivo nas margens do reservatório, atividades que devem ser controladas a fim de mitigar ações adversas que comprometam não somente a geração de energia elétrica, mas também mitigue as ações adversas geradas pela a implantação do empreendimento. A experiência foi enriquecedora pois permitiu vivenciar a atuação do geógrafo na área do bacharelado, bem como contribuir para o ambiente em nossa região.
Supervised internship report: the supervised internship experience at the Chavantes/SP hydroelectric power plant
Keywords: Meio ambiente; Licenciamento ambiental; Geografia; Usina hidrelétrica; Estágio supervisionado